2007
DOI: 10.3748/wjg.v13.i3.421
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of soluble Fas, nitric oxide and cytokines in acute decompensated cirrhotic patients

Abstract: AIM:To evaluate plasma levels of nitrite/nitrate (NOx), soluble Fas (sFas) antigen, tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6) in patients with compensated and acute decompensated cirrhosis and to evaluate mediators causing acute decompensation in liver cirrhosis. METHODS:This prospective study was conducted in the medical intensive care unit of an academic tertiary center. Fifty-five patients with acute decompensation (gastrointestinal hemorrhage, encephalopathy, hydropic decompensation) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
0
14
2
2
Order By: Relevance
“…For example, NO is a potent inducer of increased membrane permeability in the vascular endothelium and intestinal mucosa, possibly contributing to the accumulation of ascites and to bacterial translocation [31] . In the current study, although TNF-α was thought to induce NO synthesis (NOS) through the inducible NOS and endothelial NOS [32,33] , there was no significant correlation between TNF-α level and NO level in LC. This is the same to some studies, where such a relation could not be observed [34,35] .…”
Section: Cirrhotics Without Ascites (N = 27)contrasting
confidence: 59%
“…For example, NO is a potent inducer of increased membrane permeability in the vascular endothelium and intestinal mucosa, possibly contributing to the accumulation of ascites and to bacterial translocation [31] . In the current study, although TNF-α was thought to induce NO synthesis (NOS) through the inducible NOS and endothelial NOS [32,33] , there was no significant correlation between TNF-α level and NO level in LC. This is the same to some studies, where such a relation could not be observed [34,35] .…”
Section: Cirrhotics Without Ascites (N = 27)contrasting
confidence: 59%
“…Our study, including only alcoholic patients of different Child classes, strengthens previous investigations and adds further information with respect to the second messenger cGMP and its relationship with the redox state of GSH. NO • or nitrite/nitrate measurements can be affected by creatinine levels, as demonstrated recently in acute decompensated cirrhotic patients [32] . In our clinical population, patients with Child C cirrhosis had elevated creatinine values compared to those with Child A cirrhosis, and this could also influence the results.…”
Section: Nomentioning
confidence: 73%
“…• synthesis and serum levels in various cirrhotic conditions [29][30][31][32] . Our study, including only alcoholic patients of different Child classes, strengthens previous investigations and adds further information with respect to the second messenger cGMP and its relationship with the redox state of GSH.…”
Section: Nomentioning
confidence: 99%
“…In ACLF, hepatocytes are exposed to chronically elevated concentrations of inflammatory cytokines, including interferon-g, TNF-α and interleukin (IL)-2 and IL-6. Depending on levels of proapoptotic or anti-apoptotic activity, inflammatory cytokines are able to stimulate both survival and apoptosis pathways and modulate the relative equilibrium of proand anti-apoptotic proteins, such as Bad and Bcl-2 respectively [57] . Apoptosis, or 'programmed cell death' is one of two main patterns of cell death; namely apoptosis and necrosis.…”
Section: Host Response To Injury/infectionmentioning
confidence: 99%